Africa in China's global strategy - Kitissou, Marcel (African renaissance. Book series, 2007)
Globalization and fragmentation: the new era of Africa-China cooperation / Marcel Kitissou -- China's leap into the heart of the twenty first century / Michael Sachs -- Talking points on China's foreign policy / Jin Yongjian -- China's emerging interests in Africa: opportunities and challenges for Africa and the United States / Drew Thompson -- U.S. response to China's rise in Africa: policy and policy options / Raymond W. Copson -- All-weather friends in need and in deed: China-Africa relations seen from the eyes of a Chinese diplomat / Liu Guijin -- Chinese investments in Africa: a cross-cultural management perspective / John Kuada -- China's trade safari in Africa / Jean-Christophe Servant -- Bankrolling the "Going Out" strategy: China's financing of African aid and trade and implications for African debt and development / Michelle Chan-Fishel and Roxanne Lawson -- China's corporate engagement in Africa / James Reilly and Wu Na -- Growing pains and growing alliances: China, timber and Africa / Tina Butler -- Chinese drivers for African development? The effects of Chinese investments in Zambia / Peter Kragelund -- Models of development: finding relevance for Africa in China's experience of development / Stephen Little.